answersLogoWhite

0


Best Answer

X= -2

User Avatar

Wiki User

โˆ™ 2010-02-01 19:59:04
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: Simplify x plus 2
Write your answer...
Submit
Related questions

Simplify x2 plus 2x?

x(x + 2)


Simplify each expression 3 over x plus 2 plus x over x plus 2?

11+(7-3)2=


How to simplify x cube - 3x plus 2?

Assuming simplify = factor...x3 - 3x + 2 = (x-1)(x2+x-2)


How do you simplify 3x to the power of 2 plus x plus 2x to the power of 2?

3x^2 + x + 2x^2 = 5x^2 + x


Simplify x plus x plus x?

3x


X plus 2 over x plus 2 simplify?

(x+2)/(x+2) = 1x equals infinity


How do you simplify X2 plus 2x plus 4?

Factor it out: (x+2) squared


How do you simplify 6 x squared minus 2x plus 5 plus 2 x squared minus 7x - 11?

No


Simplify x squared plus 3x plus 2 divided by -3x minus x squared minus 2?

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)


Can you simplify -x-2 plus 15x?

-x - 2 + 15x = 14x - 2 = 2(7x - 1)


Simplify x plus 5 plus 4?

x + 5 + 4 = x + 9


What is 8 x plus 2 minus 4x plus 7 simplified as?

This would simplify as 4x-5


Simplify -7 plus 2(x-3)?

-7 + 2(x-3) = -7+2x-6 = 2x - 13


How do you simplify x plus 4 divided by 2?

6


How do you simplify -3x2 plus 16x plus 12?

-3x2 + 16x + 12 = -3x2 + 18x - 2x + 12 = -3x*(x - 6) - 2(x - 6) = -(3x + 2)*(x - 6)


How do you simplify x plus x plus x plus x plus y plus y plus y plus x?

The answer is 5x+3y. (5 xs and 3 ys)


4x-2 plus 5 equals 2x plus 8?

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½


What is x when 13x plus 27 equals 3x plus 32?

13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer


Simplify this expression - -x plus 3?

- - x + 3 = x + 3


Simplify -3x-6x plus x?

-9


How do you simplify x plus 2 plus x-22x plus 1?

Combine all lie term: x + x - 22x = -20x 2 + 1 = 3 So the answer is -20x +3 or 3 - 20x


What does x squared plus 4x simplify into?

x2 + 4x = x(x+4)


Simplify fully x squared minus 4x divided by x squared minus 6x plus 8?

x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)


Can you simplify x to the second power plus 2x plus 1 divided by x plus 1?

Factor the numerator. x+1 is one of its factors (otherwise, it wouldn't be possible to simplify it). Then cancel the identical factors in the numerator and the denominator.


What is used to simplify x plus 61.4?

x + 61.4 cannot be simplified.